2018
DOI: 10.1186/s41181-018-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and preclinical evaluation of a 68Ga-labelled c(RGDfK) conjugate comprising the bifunctional chelator NODIA-Me

Abstract: BackgroundWe recently developed a chelating platform based on the macrocycle 1,4,7-triazacyclononane with up to three, five-membered azaheterocyclic arms for the development of 68Ga- and 64Cu-based radiopharmaceuticals. Here, a 68Ga-labelled conjugate comprising the bifunctional chelator NODIA-Me in combination with the αvß3-targeting peptide c(RGDfK) has been synthesized and characterized. The primary aim was to evaluate further the potential of our NODIA-Me chelating system for the development of 68Ga-labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…5 Small-animal PET imaging and ex vivo biodistribution studies of corresponding 68 Ga-and 64 Cu-labeled NODIA-Me-NaI-Ahx-PSMA conjugates showed specific accumulation in PSMA-positive LNCaP tumors. 6 Both compounds exhibited rapid renal clearance with low uptake in non-target tissues confirming sufficient stability of 68 Ga-and 64 Cu(NODIA-Me) chelates in vivo. Furthermore, NODIA-Me was recently coupled to the peptide c(RGDfK) for targeting the integrin avß3 receptor.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…5 Small-animal PET imaging and ex vivo biodistribution studies of corresponding 68 Ga-and 64 Cu-labeled NODIA-Me-NaI-Ahx-PSMA conjugates showed specific accumulation in PSMA-positive LNCaP tumors. 6 Both compounds exhibited rapid renal clearance with low uptake in non-target tissues confirming sufficient stability of 68 Ga-and 64 Cu(NODIA-Me) chelates in vivo. Furthermore, NODIA-Me was recently coupled to the peptide c(RGDfK) for targeting the integrin avß3 receptor.…”
Section: Introductionmentioning
confidence: 84%
“…Besides the labeling efficiency, the stability/inertness of the radiometal complex is of importance for radiopharmaceutical applications. Hence, the stability of 111 6 The octanol/PBS partition coefficient log Doct/PBS of [ 111 In]In-13 was determined to -3.57 ± 0.01 making it slightly more lipophilic than its 64 Cu-and 68 Ga-labeled counterparts with log Doct/PBS values of -3.99 ± 0.05 and -4.27 ± 0.08, respectively.…”
Section: Indium Radiolabeling and Stability Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals and solvents were purchased from Sigma-Aldrich and TCI Europe, and used as received. The bifunctional chelator NODIA-Me 3 was prepared as previously described [ 28 , 29 ]. The peptide c(RGDfK) 7 was purchased from ABX (Radeberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The monomer 8 (Scheme 2 ) was prepared as previously described and characterization data was identical to that previously reported [ 29 ].
Scheme 2 Two synthetic routes for the preparation of the trifunctionalized NOTI-TVA 6 scaffold.
…”
Section: Methodsmentioning
confidence: 99%